Karakterisasi Bahan Anti Browning dari Ekstrak Air Buah Jambu Batu (Psidium guajava Linn) pada Buah Apel Malang (Malus sylvestris (L.) Mill) - Oktarina Husaini; Zulkifli Zulkifli; Martha L. Lande; E. Nurcahyani (Politeknik Negeri Lampung., 2017)
The purpose of this study was to prove that the water extract of guava pulp can hinder the process of browning in apples Malang. The research was conducted in October - November 2016 in the Laboratory of Plant Physiology, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Lampung. This study uses a completely randomized design (CRD) with 6 degree of concentration of water extract of the fruit flesh guava: control (Citric acid 2% w/v), 0% v/v, 25% v/v, 50% v/v, 75 % v/v, 100% v/v. Browning index is determined based on the absorbance of the extract of apple Malang at a wavelength of 420 nm. Total soluble carbohydrate content was determined by the phenol-sulfuric method, while estimating dehydrogenase enzyme activity by methylene blue method. Levene's test for homogeneity, analysis of variance and LSD test was carried out at 5% significance level. Water extract of guava fruit has the same effectiveness with citric acid 2% w/v in inhibiting browning apples Malang. Similarly, the water extract of guava fruit as well as citric acid 2% w/v has the same effect on total soluble carbohydrate content and the activity of the enzyme dehydrogenase. Water extract of guava fruit has the same effectiveness with citric acid 2% w/v except for 100% concentration on reducing sugar level. The final conclusion is that the water extract of guava fruit has the different characteristics as citric acid 2% w/v in inhibiting browning in apples Malang.